2007
DOI: 10.1086/520319
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical Models of the Solar Atmosphere. II. The Quiet‐Sun Low Chromosphere at Moderate Resolution

Abstract: We present a new, one-dimensional model of the solar atmosphere (called SRPM 305) at moderate angular resolution ($1 00 Y2 00 ). Key characteristics of the SRPM 305 model include (1) a minimum temperature of $3800 K at a gas pressure of $80 dyne cm À2 and (2) a rapid temperature rise above the temperature-minimum layer that results in substantial overionization of most elements when compared with LTE calculations. The model calculations reproduce the $4300 K minimum brightness temperature of the UV continuum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 64 publications
3
74
1
Order By: Relevance
“…If the CS97 shocks correctly represent the acoustic heating mechanism, the non-magnetic chromosphere would be essentially cold. This is contrary to the common view, derived from semi-empirical static models, of a chromosphere characterized everywhere by a steady temperature rise (Vernazza et al 1981;Fontenla et al 2007;Avrett & Loeser 2008). The failure of the CS97 model to reproduce spatially and temporally resolved quiet Sun UV observations obtained with SUMER in chromospheric lines ) has further sharpened the controversy.…”
Section: Introductioncontrasting
confidence: 64%
“…If the CS97 shocks correctly represent the acoustic heating mechanism, the non-magnetic chromosphere would be essentially cold. This is contrary to the common view, derived from semi-empirical static models, of a chromosphere characterized everywhere by a steady temperature rise (Vernazza et al 1981;Fontenla et al 2007;Avrett & Loeser 2008). The failure of the CS97 model to reproduce spatially and temporally resolved quiet Sun UV observations obtained with SUMER in chromospheric lines ) has further sharpened the controversy.…”
Section: Introductioncontrasting
confidence: 64%
“…Observations and/or models of the quiet Sun have been published by, for example, Vernazza et al (1981); Loukitcheva et al (2004);Fontenla et al (2007); Avrett & Loeser (2008), and De la Luz et al (2014). Evidence is, however, mounting that the heating of the solar chromosphere and corona is dominated by active, magnetically controlled, processes (Carlsson & Stein 1995), and it remains to be seen what quiet stellar chromosphere models could add to the more complete understanding of the physics of the Sun and other stars.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, there is not a uniform correction of the limb weakening. According to the simulated result of Jin et al (2013), who used the thin flux tube model (Fontenla et al 2006(Fontenla et al , 2007, the variation of the observed line-of-sight field conforms to the cosine function far away from the solar disk center, so the observed line-of-sight component is corrected as B B ( ) cos( ) cal obs a a = . The angle α is defined by…”
Section: Observations and Data Analysismentioning
confidence: 99%